The relative effectiveness of selected active labour market programmes and the common support problem - Stephan, Gesine; Pahnke, André (Bonn, 2008)
"For Germany, we analyse the (relative) effects of participation in several active labour market programmes on the employment prospects of participants. First, our results show that different matching algorithms result in different severe problems of common support. Second, we obtain favourable effects of participation in training programmes, which is not true for job creation schemes. Third, while lock-in effects are smaller for shorter programmes, long retraining shows mainly positive effects compared to shorter training at the end of the observation period. Fourth, participants in job creation schemes are too different from participants in training programmes to conduct a reliable comparison. "